Odpowiedź :
Odpowiedź:
[tex]18 + 2 \frac{3}{4} \times 2 \frac{2}{3} = 18 + \frac{11}{4} \times \frac{8}{3} = 18 + \frac{22}{3} = 18 + 7 \frac{1}{3} = 25 \frac{1}{3} [/tex]
[tex]1 \frac{1}{3} \div \frac{8}{9} + \frac{3}{4} \times \frac{5}{6} - 1 \frac{1}{5} \times (1 \frac{3}{8} - 1 \frac{1}{6} ) = \frac{4}{3} \times \frac{9}{8} + \frac{5}{8} - \frac{6}{5} \times (1 \frac{9}{24} - 1 \frac{4}{24} ) = \frac{3}{2} + \frac{5}{8} - \frac{6}{5} \times \frac{5}{24} = 1 \frac{1}{2} + \frac{5}{8} - \frac{1}{4} = 1 \frac{4}{8} + \frac{5}{8} - \frac{2}{8} = 1 \frac{9}{8} - \frac{2}{8} = 1 \frac{7}{8} [/tex]